« L'État de tous les spectateurs » - Irina Tcherneva (Conserveries Mémorielles)
In the beginning of the 1950s, the cinema is one of the spheres where the Soviet government undertakes reform projects: an economic development of production and distribution systems, but also a modernization of equipment and the levelling of the conditions of projection. The definition is not taboo any more, Soviet administration claims it in public: “The cinema is also a trade sphere”. The authorities justify these new political axes by spectators’ denunciation of the aesthetic and economic ineffectiveness of the Soviet cinema of the late Stalinist period. The movie theatres’ and the studios’ financial plans are based on the absolute number of spectators and screenings. So they try to redefine the figure of the Soviet spectator in comparison with Western cinema public. The methods of mobilization of the spectators, dated from the 1920s, are also revived to identify the “public needs”. The attempt to establish a form of dependence between distribution and production reveals a poor acquaintance of spectators’ tastes, the structural resistance of the cinema institution and the permanence of the values applied to social role of soviet cinema.